A high efficient map-matching algorithm for the GPS data processing intended for the highways. (2019) - Wang, Hongyu; Han, Haihua; Wang, Xiaoguang; Fang, Ruochen; Mei, Wenbo
The map-matching algorithm for the vehicle position errors correction on the digital maps is crucial in the majority of the transportation research projects based on the floating car data. This paper presents a high efficient map-matching algorithm intended for the analysis of the big data collected at the highway based on the topological characteristics of the highway road network. This algorithm has two main improvements: it uses the fuzzy estimation algorithm to reduce the redundant calculations in map-matching processing on the arterial links; and it introduces a new parameter for evaluation of the most suitable travelling path for vehicles on the highway road network. The experiment results show that the proposed map-matching algorithm improves the efficiency and assures the high accuracy of the highway GPS data processing at the same time.